Análise hierárquica de processos como ferramenta para tomada de decisão nas ações de saneamento ambiental em comunidades quilombolas - Silva Júnior, Luiz Batista da (2018)
The issue of environmental sanitation become emblematic as, over the years, advances have become unable to provide care for the entire population, especially the significant portion of the population residing in the countryside. In this context, the remaining quilombola communities are hard hit by the absence of actions that aim to solve the problems faced in their daily lives. This study describes an alternative capable of assisting decision-making processes in place of subjective methods used by public managers. The method of Analysis Hierarchical Process - AHP was applied as a tool to evaluate the conditions of rural environmental sanitation in quilombola communities, adopting as study areas the Tabacaria and Abobreiras communities, located in the State of Alagoas, in the northeast region of Brazil . Considering the criteria: sanitation services (water supply, sewage and solid waste) and socioeconomic conditions, as indicators of environmental sanitation conditions, the quilombola community Tabacaria presented worse conditions compared to the quilombola community Abobreiras. Thus, the AHP method presented itself as a robust tool in the comparative evaluation of environmental sanitation, which together with the significant simplicity of use is capable of identifying and prioritizing the most urgent demands for intervention in the adopted criteria.